2013
DOI: 10.1638/2010-0123r4.1
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF CALCIUM AND CHOLECALCIFEROL SUPPLEMENTATION ON SEVERAL PARAMETERS OF CALCIUM STATUS IN PLASMA AND URINE OF CAPTIVE ASIAN (ELEPHAS MAXIMUS) AND AFRICAN ELEPHANTS (LOXODONTA AFRICANA)

Abstract: Abstract:The aim of the current study was to assess the effect of oral calcium and cholecalciferol supplementation on several parameters of calcium status in plasma and urine of captive Asian (Elephas maximus; n ¼ 10) and African elephants (Loxodonta africana; n ¼ 6) and to detect potential species differences. Calcium and cholecalciferol supplementation were investigated in a feeding trial using a crossover design consisting of five periods of 28 days each in summer. From days 28-56 (period 2), elephants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…Importantly, zoo elephant research has repeatedly identified differences between African and Asian elephants. Different drug‐dosage requirements (Bechert et al ., ), reproductive pathologies (Hildebrandt et al ., ; Brown et al ., ), digestive physiologies (Dierenfeld, ; van Sonsbeek et al ., ), pheromones (Rasmussen & Schulte, ) and susceptibility to EEHV (Bronson, E., et al ., ) are a few such examples. Nonetheless, African and Asian elephants have typically been viewed and managed collectively as ‘elephants’ in captive settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, zoo elephant research has repeatedly identified differences between African and Asian elephants. Different drug‐dosage requirements (Bechert et al ., ), reproductive pathologies (Hildebrandt et al ., ; Brown et al ., ), digestive physiologies (Dierenfeld, ; van Sonsbeek et al ., ), pheromones (Rasmussen & Schulte, ) and susceptibility to EEHV (Bronson, E., et al ., ) are a few such examples. Nonetheless, African and Asian elephants have typically been viewed and managed collectively as ‘elephants’ in captive settings.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, dietary supplementation with vitamin E is required to match values found in free‐ranging elephants, and there also appears to be a species‐specific response to vitamin E (Swanson et al ., ) that requires further investigation. Vitamin D and calcium dynamics in both species of elephants have been eloquently examined by seasonal studies and supplementation in a zoo setting (van Sonsbeek et al ., ). Species‐specific responses were documented, which may relate to habitats and available nutrient resources within which each species evolved (van Sonsbeek et al ., ).…”
Section: Nutritionmentioning
confidence: 97%
See 1 more Smart Citation
“…Research has also been carried out into hypocalcaemia in captive elephants, because there are some indications that hypocalcaemia is associated with dystocia (difficult births) (van Sonsbeek et al , ). Although causality between hypocalcaemia and dystocia in elephants is still unproven, it has been reported in other species, such as cattle and sheep, and there are some indications that this relationship also applies in elephants (Stubbings, ; Smith & Risco, ; van Sonsbeek et al , ). Therefore, veterinary experts recommend that elephants are provided with more calcium and cholecalciferol than was prescribed by previous guidelines (van Sonsbeek et al , ).…”
Section: Developmentsmentioning
confidence: 99%
“…Asian elephants also have fewer ribs, more molar plates and a small intestine twice as long as that in African elephants [1,2,4]. The elephant species also differ in their nutritional needs [5] and susceptibility to infectious diseases [6]. …”
Section: Data Descriptionmentioning
confidence: 99%